Prebiotic xylo-oligosaccharides as high-value co-products on an integrated biorefinery approach from lignocellulosic feedstock - Moura, Patrícia (2009)
The present work proposes the production of prebiotic xylo-oligosaccharides (XOS) as high-value co-products of the Lignocellulose Feedstock Biorefinery concept, foreseeing potential applications on food, feed and nutraceutical industries. Autohydrolysis was used to selectively solubilise the hemicellulosic fraction of several xylan-rich, widely available, agricultural, agro-industrial and forestry by-products: corn cobs, brewery’s spent grain and Eucalyptus wood chips. The soluble hemicellulose-rich and the solid cellulose- and lignin-rich fractions were separated, and the crude XOS-rich hydrolysates were further purified by gel filtration chromatography. Selected fractions of purified XOS within the desired ranges of polymerization degree were characterised and their prebiotic potential was investigated in in vitro fermentations by bifidobacteria, lactobacilli and intestinal inocula. Parameters such as bacterial growth and XOS consumption were evaluated and compared with commercially available xylo-oligosaccharides. The differences observed were considered of relevance for the formulation of symbiotic preparations and the future design of targeted, tailor-made prebiotic xylo-oligosaccharides.